Practices of Open and Distance Education in Nepal : Opportunities and Challenges - Arjun Neupane, (Interdisciplinary Research in Education, 2021)
The purpose of this study was to explore the opportunities and challenges of open and distance learning (ODL) system and to explore the gateway for the implementation of ODL to optimizing the opportunities in policy and implementation in higher education of Nepal. To achieve the goal, explanatory sequential research design was used. Questionnaire form and interview schedule were the tools of the study. The findings revealed that students have positive perceptions towards the use of open and distance learning mode. The benefits accruing from technology usage include: improved access, interaction with teachers as well as other students, access to a wide variety of recent and updated resources that are available online as well as contents ha ring. Challenges faced by both the teachers and the learners were unreliable internet accesses, techno phobia and inadequate pedagogical skills of online teachers. Some of the challenges are academic, some are administrative and some others are Information and Communication Technology (ICT) related. It is suggested that online friendly curriculum has to be developed for ODL mode that must be focused on the ICT integration in the subject areas.